The Effect of the Addition of Core Exercises to Supervised Physiotherapy in Patients With Subacromial Impingement Syndrome - Héctor Gutiérrez-Espinoza; Guillermo Méndez-Rebolledo; Jonathan Zavala-González; Serghio Torreblanca-Vargas; Felipe Araya-Quintanilla (International Journal of Sports Physical Therapy)
# Background